A 2D numerical modelling of plasticity induced crack closure on MT specimens. (December 2022) - Esteves, Carlos; Braga, Daniel F.O.; Farahani, Behzad V.; Moreira, Pedro M.G.P.; Baptista, Ricardo; Infante, Virginia
Highlights: Middle tension specimens were fatigued to build fatigue cracks. The cracked specimens were monotonically loaded at the maximum load. The experimental data was collected by 2D DIC. The problem was solved using 2D FEM. Fracture parameters and variational fields were studied and validated. Abstract: In many engineering fields, structures are often subjected to fatigue loading that initiate and propagate cracks. The development of fracture mechanics studies has enabled the tolerance of a substantial amount of damage and the ability to predict failure in fatigue damaged structures, extending their service life safely. This can bring social impacts from economics, public-safety, or an environmental point of view. These damage tolerance analyses can be performed using linear elastic fracture mechanics (LEFM), where the Stress Intensity Factor (SIF) is a chief key, or under elastoplastic fracture mechanics (EPFM), where plasticity induced crack closure (PICC) plays a major role on fatigue crack growth (FCG). This study deals with the computational modelling developed consisting in the simulation of a two-dimensional model to predict FCG under PICC conditions. Extremely fine meshes were generated around the crack tip, in order to predict PICC loads, SIF and plastic zone size. The results showed good agreement with the experimental model, allowing for accurate damage tolerance assessments.